2014
DOI: 10.1007/s11904-014-0222-z
|View full text |Cite
|
Sign up to set email alerts
|

Host Genetic Factors Predisposing to HIV-Associated Neurocognitive Disorder

Abstract: The success of combination antiretroviral therapy (cART) in transforming the lives of HIV-infected individuals with access to these drugs is tempered by the increasing threat of HIV-associated neurocognitive disorders (HAND) to their overall health and quality of life. Intensive investigations over the past two decades have underscored the role of host immune responses, inflammation, and monocyte-derived macrophages in HAND, but the precise pathogenic mechanisms underlying HAND remain only partially delineated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 144 publications
1
42
0
Order By: Relevance
“…Despite its potential role in HAND, there are no published studies of DNAm in this context. Indeed, there are very few studies overall on epigenetics and HAND(Desplats et al, 2013; Kazantsev & Thompson, 2008; Mukerjee et al, 2011; Narasipura, Kim, & Al-Harthi, 2014; Saiyed et al, 2011; Sun, Spencer, Chen, Li, & Davie, 2003; Tatro et al, 2010), as recently reviewed (Kallianpur & Levine, 2014; Levine et al, 2014). To our knowledge there have been no peer-reviewed studies examining global (i.e., genome-wide) DNAm in the context of HAND (Perez-Santiago J, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its potential role in HAND, there are no published studies of DNAm in this context. Indeed, there are very few studies overall on epigenetics and HAND(Desplats et al, 2013; Kazantsev & Thompson, 2008; Mukerjee et al, 2011; Narasipura, Kim, & Al-Harthi, 2014; Saiyed et al, 2011; Sun, Spencer, Chen, Li, & Davie, 2003; Tatro et al, 2010), as recently reviewed (Kallianpur & Levine, 2014; Levine et al, 2014). To our knowledge there have been no peer-reviewed studies examining global (i.e., genome-wide) DNAm in the context of HAND (Perez-Santiago J, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We calculated the CPE, a score that is based on the pharmacokinetic and pharmacodynamic characteristics of antiretroviral medications (Letendre, 2011). CPE scores for the regimen reported at the time of neurocognitive testing were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro studies have identified the neurotoxic effects of viral proteins, inflammatory and metabolic agents; however, critical factors contributing to neuropathogenesis in vivo are not completely understood. Polymorphism in TNF-α gene that results in increased secretion in response to bacterial lipopolysaccharide has been observed with increased frequency in HIV-1 seropositive individuals with dementia [16], whereas, mutation in CCL2 (at position 2578G), CCR5Δ32 and other host factors have been identified as neuroprotective[1, 1719]. While recent work has studied the expression of microRNAs (miRNA) in HAND response [2024] relatively little is known about their regulatory role and their targets.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that host genetic polymorphisms influence the risk of developing numerous diseases in HIV-infected people. [16][17][18] Estrogene hormone is well known to play an essential role in the growth and development during childhood and estrogen receptors (ERs) mediate much estrogen action.…”
Section: Discussionmentioning
confidence: 99%